The Impact of Regional Revenue and Expenditure Budget (APBD) Deficits on Fiscal Sustainability and Government Performance in Pangandaran Regency - Farida, Ai Siti; Suhendar, Suhendar (Pusjar SKPP Lembaga Administrasi Negara, 2026)
The deficit in the Regional Revenue and Expenditure Budget (APBD) poses a critical challenge to fiscal sustainability in Pangandaran Regency. This study aims to analyse the impact of the APBD deficit on local governance by examining the causes, implications, and potential strategies to improve fiscal stability. A descriptive qualitative approach was used, with document analysis as the main method. Data were collected from official documents of the Pangandaran Regency Government, including regional regulations related to the 2021–2025 APBD, as well as from academic literature published on Google Scholar, academic portals, and other reliable sources between 2010 and 2025. The study results showthat the APBD deficit in Pangandaran follows a recurring pattern, with the highest level reaching 35.50% of total revenue in 2023. This region remains heavily dependent on transfers from the central government, which account for more than 77% of its annual revenue. Expenditures are mostly directed towards personnel and operational costs, while capital expenditures are trending downward. From the perspective of Public Finance Theory, Fiscal Decentralization Theory, and Fiscal Sustainability Theory, this condition poses a risk to regional fiscal capacity and may hamper long-term economic development. To address these challenges, this study recommends practical strategies: optimizing Local Own-Source Revenue (PAD) through tourism and creative industries; reallocating expenditures toward productive capital investments; and implementing performance-based budgeting to strengthen fiscal discipline. The contribution of this study lies in providing theoretical insights and concrete policy recommendations in public administration, particularly in strengthening regional fiscal independence and resilience in managing recurring budget deficits.